(untitled) (Ustozlar uchun, 2026)
In the modern digital era, people are more connected than ever through technology and social media. However, despite these advancements, loneliness has become a growing global issue. Many researchers describe this situation as a “loneliness epidemic.” This article explores the causes of loneliness in the digital age, the role of social media, its effects on mental and physical health, and possible solutions to reduce loneliness in modern society.